Test Levels of Protein, Fiber and Organoleptic Tempeh Cake as an Alternative Snack for Diabetes Mellitus (DM) Patients - Nurman, Zurni; Ismanilda, Ismanilda; Yuska, Defniwita; Puri, Ice Yolanda (Sarana Ilmu Indonesia (salnesia), 2024)
The incidence of Diabetes Mellitus (DM) in Indonesia continues to increase. WHO reported a DM prevalence of 7% in Indonesia in 2013, while West Sumatra rose from 1,3% in 2013 to 1,8% in 2018. One of the efforts to address DM is food diversification, such as making cake from tempeh. This research aimed to determined tempeh cake's protein, fiber, and organoleptic quality. This type of research was an experiment using a Completely Randomized Design with 1 control (without tempeh) and 3 treatments (tempeh at 25g, 50g, and 75g), each with 2 replications for the organoleptic test. The best result from the organoleptic test was tested for protein content and fiber content. The research was carried out in July – November 2022 in the IBM laboratory, Department of Nutrition, Health Polytechnic, Ministry of Health, Padang, while protein and fiber analysis was carried out at the Industrial Research and Standardization Center in Padang. Observations included organoleptic quality (color, aroma, texture, taste) using a hedonic test, analyzed with the Kruskal-Wallis test and followed by the Mann-Whitney test if significant. The results showed that tempeh supplementation affected the color, aroma, texture, and taste of the cake. The best cake was with 50g tempeh addition (18,74% protein, 28,18% fiber). Panelists could distinguish the organoleptic characteristics of cakes with tempeh. The research concludes that tempeh addition increases the protein and fiber content of the cake. It is recommended to apply tempeh cake as a snack for DM patients, research its glycemic index, and evaluate its shelf life.